Effects of Cooling Rates on Self-Assembling Structures of 12-Hydroxystearic Acid in an Ionic Liquid - Hiroyuki Takeno; Mai Kozuka (Advances in Materials Science and Engineering)
We investigated effects of cooling rates on self-assembling structures and mechanical and electrochemical properties of 12-hydroxystearic acid (12-HSA) in an ionic liquid (IL), 1-allyl-3-butylimidazolium bis(trifluoromethanesulfonyl) imide ([ABIm][TFSI]). The mixture of 12-HSA with [ABIm][TFSI] had an upper critical solution temperature (UCST) above the sol-gel transition temperature, and the microstructure of the ionogel was significantly affected by cooling rates, where it was prepared. The twisted self-assembling structure was formed during a slow cooling process at a rate of 0.4°C/min, whereas spherical domains caused by the liquid-liquid phase separation and radiate fibrous structure were observed for the quenched gel. The real-time small-angle X-ray scattering (SAXS) measurements for the ionogel during a slow cooling process at a rate of 0.4°C/min presented three different (001) peaks arising from long spacings of 46.5, 42.4, and 39.7 Å, which were also observed for SAXS curves of a neat 12-HSA. These results suggest that three polymorphic forms of 12-HSA are formed in the IL. The polymorphic form significantly affected the mechanical properties of the ionogel, whereas it did not affect the ionic conductivity. The ionic conductivity of the ionogel was close to that of a neat [ABIm][TFSI] irrespective of the polymorphic forms of 12-HSA.